Establishing Immunohistochemistry Protocols in Early Neonatal Rat Brains for RXRÎ³: A Labile Biological Target - Islam, Sobia; Jehangir, Fouzia; Rashid, Nadia; Rashid, Sadia; Akhtar, Lubna (ADVANCES IN BASIC MEDICAL SCIENCES, 2020)
Background: Vitamin A is very important for development of multiple organ systems in the body. Retinoid X receptor Î³ (RXRÎ³) is one of the nuclear receptors through which vitamin A helps in various biological processes. We experimented to show expression of RXRÎ³ through immunohistochemistry in early neonatal rat brains. Methodology: A series of experiments were carried out to optimize the immunohistochemistry protocols for RXRÎ³ in early neonatal rat brains. Immunohistochemistry protocol for RXRÎ³ was modified from the protocol available for adult rat brain in literature. We have done RXRÎ³ immunohistochemistry for rat brains at the ages of 3, 10, 18 and 60 days. We have compared the immunostaining with the nissle-stained sections of the same brains to show the staining pattern of RXRÎ³ immunohistochemistry. Results: Our experiments revealed characteristics of immunostaining for RXRÎ³. It was shown that RXRÎ³ protein was present in the cytoplasm as well as nuclei. The cellular processes also took the immunostain. Additionally, our immunohistochemistry results clearly showed that more cells are visible through Nissle staining as compared to RXRÎ³ immunohistochemistry. Conclusion: We could present expression of RXRÎ³ in early neonatal and adult rat brains through immunohistochemistry. We have documented the sensitivity of RXRÎ³ to various commonly practiced methodological components for immunohistochemistry. Our study has not only developed a successful immunohistochemistry protocol for RXRÎ³ in early neonatal rat brains but it may help future researchers to tackle sensitive proteins for immunohistochemistry.